SOCIALIZATION OF DIGITAL LITERACY AS AN EFFORT TO APPRECIATE OTHER PEOPLE'S WORK OR CONTENT ON SOCIAL MEDIA - Herman Herman; Melvin M. Simanjuntak; Ernest Grace; Elly Susanti; Nelly Ervina (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
This community service activity was carried out with the aim of providing socialization for efforts to respect the content/work of others on social media. This activity was organized by KOMINFO Indonesia Maju with the main theme being the 2021 Digital Literacy National Movement. This activity was held on Wednesday, 17 November 2021 at 13.00 WIB until it was finished. This activity is carried out online through the zoom application. About 200 participants took part in this webinar activity. The target of the socialization is the people who live in the city of Pematang Siantar, North Sumatra Province. The results obtained from this webinar activity are increasing awareness and also digital literacy competence which is the most important milestone in educating social media users in ethics, especially in avoiding plagiarism of content or other people's work on social media which can have a negative impact on its users itself